The Relationship Between Parental Social Restriction and Adolescent Social Development at SMPN 2 Cisitu - Ariani Nuranisa Agustian; Anggi Setia Lengkana; Entan Saptani (Journal Coaching Education Sports, 2026)
This study aimed to examine the relationship between parental social restriction and adolescent social development at SMPN 2 Cisitu. The study employed a quantitative correlational design supported by interview data to strengthen the interpretation of statistical findings. The participants consisted of 30 junior high school students from grades VII, VIII, and IX, along with three homeroom teachers and three parents as supporting informants. Data were collected using questionnaires and semi-structured interviews. Statistical analysis included descriptive statistics, normality testing, Spearman correlation, and simple linear regression. The findings showed that parental social restriction had a positive but non-significant relationship with adolescent social development. The Spearman correlation coefficient indicated a low positive relationship that was not statistically significant. Interview findings revealed that parents generally implemented social restrictions through supervision of peer relationships, playtime regulation, and guidance in selecting friends. Teachers and parents perceived these restrictions as beneficial for monitoring adolescents’ social behavior; however, excessive restriction was also considered capable of reducing adolescents’ confidence and social independence. The study highlights that balanced parental supervision combined with communication and emotional support may contribute more effectively to adolescents’ social adjustment and interaction.